Exports, Imports, Inflation, BI Rates and Their Implications for Indonesia Composite Index (ICI) in Indonesia 2018-2022 - Muhammad Ali; Ikram, Syafrizal; Suryana, Suryana; Arnan, Sendi Gusnandar (Technium Business and Management, 2024)
The purpose of this study is to ascertain the impact of imports, exports, inflation, and BI rates on Indonesia Composite Index (ICI) over the years 2018–2022. This study’s findings are discussed in relation to inflation, imports, exports, BI rates, and ICI. Theories pertaining to that field are the method used in this regard. This study was carried out in Indonesia. Research of this kind is quantitative in nature. Central Agency of Statistics provided time series secondary data for this study in the form of publications on imports, exports, inflation, BI rates, and ICI for the period of January 2018 to December 2022.The explanatory approach was the research methodology employed in this study. Multiple linear regression analysis and descriptive analysis are the data analysis methods used in this study. The study’s findings partially indicate that while imports and inflation have little bearing on the ICI, exports and BI rates do. The study’s findings concurrently demonstrate that the ICI is impacted by inflation, imports, exports, and BI rates.